1975
DOI: 10.1530/acta.0.0790164
|View full text |Cite
|
Sign up to set email alerts
|

TESTOSTERONE 5α-Reduction IN THE SKIN OF NORMAL SUBJECTS AND OF PATIENTS WITH ABNORMAL SEX DEVELOPMENT

Abstract: Human pubic skin was obtained from normal subjects and patients with abnormal sex differentiation. Skin samples (200 mg) supplemented with NADPH, were incubated for 1 h with labelled testosterone. The conversion of testosterone to dihydrotestosterone1), 3\g=a\-and 3\g=b\-androstanediol was calculated. This conversion averaged 14.9 \m=+-\ 3.4 % (se) in 11 normal men and 3.6 \ m=+-\1.4 % (se) in 8 normal women. In 4 children as in 4 young hypogonadotrophic hypogonadal men, the conversion rate of testosterone to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

1976
1976
1989
1989

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(17 citation statements)
references
References 7 publications
(10 reference statements)
2
14
0
1
Order By: Relevance
“…Recent studies with cultured human skin fibroblasts have suggested that 5c~-reductase activity may be androgen-dependent (23), similar to that reported for pubic skin homogenates by the same investigators (24,25). Enzyme activity from male foreskin fibroblasts was higher than from female pubic skin fibroblasts, with intermediate levels observed for pubic skin fibroblasts from hirsute women (23).…”
Section: 5e~-reductase Activity In Normal Skin Fibroblastssupporting
confidence: 80%
“…Recent studies with cultured human skin fibroblasts have suggested that 5c~-reductase activity may be androgen-dependent (23), similar to that reported for pubic skin homogenates by the same investigators (24,25). Enzyme activity from male foreskin fibroblasts was higher than from female pubic skin fibroblasts, with intermediate levels observed for pubic skin fibroblasts from hirsute women (23).…”
Section: 5e~-reductase Activity In Normal Skin Fibroblastssupporting
confidence: 80%
“…the pubic area) and barely detectable in pubic skin homogenates of patients with complete androgen insensitivity, hypogonadal males, and prepubertal children. In children, a pubertal increase in 5a-reductase activity in pubic skin was noted, concomitant with a pubertal increase in circulating androgens (34,51). In contrast, in genital (labial) skin homogenates of adult subjects with complete androgen insensitivity, normal 5a-reductase activity was found.…”
Section: Discussionmentioning
confidence: 97%
“…These data imply that in TF subjects, the decreased 5a-reductase(s) activity is mainly peripheral rather than splanchnic in origin. It has been demonstrated that 5a-reductase activity is barely detectable in pubic skin of patients with TF (14). It has also been shown that in normal fibroblasts cultured from pubic skin, DHT binding to the cytosol receptor can increase 5a-reductase activity.…”
Section: Controls (N-40)mentioning
confidence: 99%